Gap Junctions in A8 Amacrine Cells Are Made of Connexin36 but Are Differently Regulated Than Gap Junctions in AII Amacrine Cells - Yadav, Shubhash C.; Tetenborg, Stephan; Dedek, Karin (Frontiers in Molecular Neuroscience, 2019)
In the mammalian retina, amacrine cells represent the most diverse cell class and are involved in the spatio-temporal processing of visual signals in the inner plexiform layer. They are connected to bipolar, other amacrine and ganglion cells, forming complex networks via electrical and chemical synapses. The small-field A8 amacrine cell was shown to receive non-selective glutamatergic input from OFF and ON cone bipolar cells at its bistratified dendrites in sublamina 1 and 4 of the inner plexiform layer. Interestingly, it was also shown to form electrical synapses with ON cone bipolar cells, thus resembling the rod pathway-specific AII amacrine cell. In contrast to the AII cell, however, the electrical synapses of A8 cells are poorly understood. Therefore, we made use of the Ier5-GFP mouse line, in which A8 cells are labeled by GFP, to study the gap junction composition and frequency in A8 cells. We found that A8 cells form <20 gap junctions per cell and these gap junctions consist of connexin36. Connexin36 is present at both OFF and ON dendrites of A8 cells, preferentially connecting A8 cells to type 1 OFF and type 6 and 7 ON bipolar cells and presumably other amacrine cells. Additionally, we show that the OFF dendrites of A8 cells co-stratify with the processes of dopaminergic amacrine cells from which they may receive GABAergic input via GABAA receptor subunit α3. As we found A8 cells to express dopamine receptor D1 (but not D2), we also tested whether A8 cell coupling is modulated by D1 receptor agonists and antagonists as was shown for the coupling of AII cells. However, this was not the case. In summary, our data suggests that A8 coupling is differently regulated than AII cells and may even be independent of ambient light levels and serve signal facilitation rather than providing a separate neuronal pathway.